Perforated Corneal Ulcer and Iris Oculi Sinistra Prolapse - Fitriani Antika Dhamayanti; Rani Himayani; Helmi Ismunandar (Medula, 2020)
Corneal ulcer is a pathological condition of the cornea characterized by suppurative infiltrates accompanied by a resonating corneal defect,corneal tissue discontinuity that can occur from the epithelium to the stroma. Corneal ulcers can occur due to trauma by foreign objects or diseases that cause the entry of bacteria or fungi into the cornea, causing infection or inflammation. Mr. 90 years old came with complaints that the left eye cannot see accompanied by bleeding out of clot. This complaint begins with the trauma he experienced since 1 week ago. Complaints that are felt by red eyes (+), pain (+), blurred vision (+), glare (+), swelling of the eyelids (+) and then a fluid in the form of blood and white fluid accompanied by thick yellowish from his left eye. On physical examination obtained ophthalmological status obtained 6/60 right eye vision, left eye vision zero visual field. In the superior palpebra et inferior oculi sinistra there is edema (+), NLP vision, conjunctival injection (+), ciliary injection (+), corneal perforation and cloudy stromal infiltrate (+), prolapsed iris with blood clots and yellowish fluid. The treatment given to these patients is in the form of operative and non-operative management. The operative action performed on this patient is oculi sinistra eviseration. The non-operative action taken is Ceftriaxone 2x1 gram injection, As. Mefenamat 3x500mg, Ranitidine 2x1 amp, Gentamicin Salp.